2011
DOI: 10.1039/c0cc04698a
|View full text |Cite
|
Sign up to set email alerts
|

A concise total synthesis of (±)-cipadonoid B from synthetic azedaralide

Abstract: The tetranortriterpene cipadonoid B was efficiently constructed from synthetic azedaralide in a one-pot cascade, via the underutilised ketal-Claisen rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…2 The final solution, forming this bond by an intramolecular reaction (in this case a sigmatropic rearrangement), is the standard method to surmount this challenge. 6 Much less common is the use of a bimolecular reaction to join two complex fragments and form two new stereocenters, at least one of which is quaternary. 7,8 Reactions between nucleophilic carbon radicals and electrondeficient alkenes have several attractive features for use in coupling of complex fragments, and in particular, tertiary carbon radicals are especially well-suited for forming quaternary stereocenters by uniting complex fragments through sp 3 −sp 3 σ bonds.…”
Section: Introductionmentioning
confidence: 99%
“…2 The final solution, forming this bond by an intramolecular reaction (in this case a sigmatropic rearrangement), is the standard method to surmount this challenge. 6 Much less common is the use of a bimolecular reaction to join two complex fragments and form two new stereocenters, at least one of which is quaternary. 7,8 Reactions between nucleophilic carbon radicals and electrondeficient alkenes have several attractive features for use in coupling of complex fragments, and in particular, tertiary carbon radicals are especially well-suited for forming quaternary stereocenters by uniting complex fragments through sp 3 −sp 3 σ bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Based upon cipadonoid B 359, 118 Faber et al further reported a concise and enantioselective total synthesis of proceranolide 364, khayasin 365 and mexicanolide 366 (Scheme 2). First, compound 364 was obtained from 370 by epoxidation and cyclization; then, compound 365 was afforded by acylation of 364; nally, conversion of 364 to 366 in the presence of Jones reagent was achieved.…”
Section: Khayasin Proceranolide and Mexicanolidementioning
confidence: 99%
“…The intact limonoid framework is characterized by a 4,4,8‐trimethyl‐17‐furyl‐13α‐androstane, but this family encompasses a diverse array of structural architectures as a result of oxidations and skeletal rearrangements. Not surprisingly, the unique architectures and the wide spectrum of biological properties of limonoids have attracted keen interest from the synthesis community,4 and for example, azadiradione,5 cipadonoid,6a mexicanolides,6b and azadirachtin have been synthesized 7. Herein, we describe the first total synthesis of (±)‐limonin ( 1 ).…”
Section: Methodsmentioning
confidence: 99%